The company human capital’s role in the export of SMEs based on the global competitiveness project - Sipos, Norbert; Venczel-Szakó, Tímea; Bankó, Zoltán (Vezetéstudomány / Budapest Management Review, 2024)
This research examines the role of company human capital factors in the export activities of small and medium-sized enterprises (SMEs) in an international context. The authors hypothesize that the main barriers to SME export lie in internal company factors, which can be effectively analysed using the resource-based view (RBV) approach. Research focused on SMEs is limited, especially in developing economies. The results contribute to a deeper understanding of the role of RBV elements of company human capital in export activities. The analysis is based on data from surveys conducted between 2018 and 2023 within the framework of the Global Competitiveness Project. The results highlight that knowledge of target markets and foreign language skills are essential for export success. Additionally, well-developed internal administrative routines and processes are crucial. Employee-related issues can act as significant obstacles, so internal conflicts must be addressed first. Fine-tuning incentive systems positively contribute to SME export performance.